Post-streptococcal myositis - ultrasound features of an under-recognised disorder: a case report - Benedict Grießmann; Kirsten de Groot (BMC Musculoskeletal Disorders)
Abstract Background Post-streptococcal myalgia and myositis are very rare complications of streptococcal infections with group A β-haemolytic streptococci. Data on this condition are scarce and even less is known about findings in clinical imaging. Until today, there are no descriptions of ultrasonographic changes in this condition. Case presentation We present a case of a 31-year-old female patient with immobilizing myalgia of the left outer thigh following a streptococcal upper respiratory tract infection, accompanied with erythemata nodosa on both shins. Laboratory results indicated post-streptococcal myositis since Creatine kinase, Lactate dehydrogenase and Antistreptolysin antibodies were significantly elevated. An ultrasound of the affected vastus medialis of the left quadriceps femoris muscle was performed, which showed a focal increase in muscle echogenicity with loss of architecture and hypervascularisation in Power Doppler Mode. The diagnosis of focal myositis was confirmed with magnetic resonance imaging. The patient’s symptoms as well as the ultrasonographic changes fully resolved under therapy with Ibuprofen and intravenous Ampicillin/Sulbactam. Conclusions This is the first description of ultrasound findings in this rare condition. We conclude that muscular ultrasound is helpful to identify myositis in post-streptococcal myalgia and myositis.